Consensus Indices of Two-Layered Multi-Star Networks: An Application of Laplacian Spectrum - Huang, Da; Bian, Jicheng; Jiang, Haijun; Yu, Zhiyong (Frontiers in Physics, 2021)
In this article, the convergence speed and robustness of the consensus for several dual layered star-composed multi-agent networks are studied through the method of graph spectra. The consensus related indices which can measure the performance of the coordination systems refer to the algebraic connectivity of the graph and the network coherence. In particular, graph operations are introduced to construct several novel two-layered networks, and the methods of graph spectra is applied to derive the network coherence for the multi-agent networks, and we find that the adhering of star topologies will make the first order coherence of the duallayer systems increase some constants in the sense of limit computations. To the second order case, asymptotic properties also exist when the index is divided by the number of leaf nodes. Finally, the consensus related indices of the duplex networks with the same number of nodes but non-isomorphic structures have been compared and simulated, and it is found that both the first and second order coherence of the network D are between A and B, C has the best first order robustness, but it behaves the worst robustness in the second order case.